The Tendency of Cyberbullying Behavior in Terms of Gender of Students - Amanda Lucya Marneta; Indah Sukmawati (Consilium, 2021)
Cyberbullying is a bad phenomenon that has negative implications for a person and is also a worse form of bullying than bullying in the real world. Gender is one of the factors that influence cyberbullying. Some studies say there are differences in cyberbullying behavior between boys and girls. This study aims to describe the trend of cyberbullying behavior of male students and female students of SMPN 10 Padang. The tendency of Cyberbullying Behavior can be seen from the difference in gender. This study uses a comparative descriptive technique. The population used was Class VII, VIII, IX SMP N 10 Padang with a sample size of 268. The sampling technique used was proportional stratified random sampling. The technique of collecting data is by distributing questionnaires. Data were tested with descriptive analysis and differential analysis in the form of t test or t-test. The results showed that, the tendency of cyberbullying behavior of SMP N 10 Padang students was generally in the medium and low categories. The tendency of male students to be cyberbullying behavior is generally in the medium and low categories. The tendency of female students to be cyberbullying behavior is generally in the medium category. There is a significant difference between the tendency of male students 'cyberbullying behavior and female students where the tendency of male students' cyberbullying behavior is lower than the tendency of female students to cyberbullying behavior with a total percentage of male students 22.0% and female students 24.0%.